Immunomodulatory activity of omadacycline in vitro and in a murine model of acute lung injury - Madeline Sanders; Paul Beringer (mSphere)
ABSTRACT Cystic fibrosis (CF) is characterized by chronic airway obstruction, infection, and inflammation leading to progressive loss of lung function and eventual respiratory failure. Omadacycline, a tetracycline antibiotic, demonstrates in vitro activity against key CF pathogens, substantial lung penetration, and increasing clinical evidence for the treatment of lung infections in people with CF (PwCF). Preliminary in vitro data demonstrate that omadacycline exhibits anti-inflammatory activity. This study aims to determine the anti-inflammatory effects of omadacycline in vitro and in a murine model of lipopolysaccharide (LPS)-induced lung neutrophilia. In vitro, THP-1-derived macrophages were treated with omadacycline (20–100 µg/mL) 30 minutes prior to LPS stimulation. Pro-inflammatory cytokine (TNF-α, IL-1β/6), chemokine (CXCL-1/2), and MMP-9 levels were analyzed after 24 hours by ELISA. Omadacycline’s effects on IL-8-induced human neutrophil chemotaxis were also investigated. In vivo, omadacycline (2.5–30 mg/kg), comparators dexamethasone (1 mg/kg), and azithromycin (30 mg/kg) were administered 1 hour before and 6 hours after intranasal LPS challenge, respectively. Leukocyte counts and differentials in bronchoalveolar lavage fluid (BALF), inflammatory mediator levels in BALF and lung homogenates, pulmonary edema markers, and the severity of lung injury were evaluated 24 hours or 48 hours post-challenge. Treatment with omadacycline in vitro resulted in significant, dose-dependent reductions in IL-6, CXCL-1, and MMP-9 expression and inhibition of IL-8-induced neutrophil chemotaxis. In vivo, omadacycline yielded protective and therapeutic effects by reducing the production of proinflammatory cytokines and chemokines and neutrophil infiltration into the lungs, along with modestly improving lung injury severity. These preclinical results suggest that omadacycline may provide dual anti-bacterial and anti-inflammatory activities relevant to chronic lung infection treatment in PwCF.IMPORTANCENontuberculous mycobacteria, particularly Mycobacterium abscessus complex (MABSC), are a major concern for people with cystic fibrosis (PwCF) due to their association with deteriorating lung function. A substantial barrier to effective treatment is the limited number of safe and effective antibiotics. Omadacycline offers a potential advancement in managing MABSC infections in cystic fibrosis due to its activity, effective penetration into pulmonary secretions, improved tolerability, and good oral bioavailability as shown in healthy volunteers. Our study is the first to explore omadacycline’s effects in a model of sterile lung inflammation and acute lung injury. We found that omadacycline not only has potent anti-bacterial properties but also exhibits anti-inflammatory effects, reducing lung inflammation and injury in our preclinical models. These findings underscore omadacycline’s potential as a dual-action therapy for lung infections in PwCF, indicating significant potential to improve patient outcomes and guide more effective antimicrobial therapy decisions.